PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERPERSEPSI TERHADAP KINERJA KARYAWAN ( STUDI PADA PDAM TIRTA MOEDAL SEMARANG ) - Chindy Chintia Margaret Gultom, 12.05.51.0135 (Students Journal of Economic and Management, 2016)
This study aims to identify factors that affect the performance of employees at PDAM Tirta Moedal Semarang. These factors are motivation, work discipline and perceived organizational culture. High motivation can improve employee performance of PDAM Tirta Moedal Semarang. This study uses primary data that is questionnaire. The population is 515 employees. Meanwhile the sample is 135 respondents. Prior to tha analysis, test of validity and reliability of the quesstionnaire is conducted. Furthermore, hypotheses testing use SPSS version 20. Based on the regression test, it is known that motivation, work dicipline and perceived organisational culture affect positively and significantly on employee performance. The value of r-square is 63,3%. It means that 63,3% of Y variable can be explained by the independent variables. The rest explained by other variables outside of the model. Keywords: motivation, work discipline, Perceived Organizational Culture and employe performance.